Toxoplasmosis: Epidemiology, Diagnosis, Treatment - A. A. Khryanin; O. V. Reshetnikov; I. N. Kuvshinova (Антибиотики и Химиотерапия, 2020)
The up-to-date literature and original data on the epidemiology, diagnosis and treatment of toxoplasmosis are presented. Particular attention is paid to the parasite infection during pregnancy. Spiramycin is the drug of choice for acute toxoplasmosis in pregnant women.